2015
DOI: 10.1093/ijnp/pyv093
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetoencephalographic Correlates of Emotional Processing in Major Depression Before and After Pharmacological Treatment

Abstract: Background:In major depressive disorder (MDD), electrophysiological and imaging studies suggest reduced neural activity in the parietal and dorsolateral prefrontal cortex regions. In the present study, neural correlates of emotional processing in MDD were analyzed for the first time in a pre-/post-treatment design by means of magnetoencephalography (MEG), allowing for detecting temporal dynamics of brain activation.Methods:Twenty-five medication-free Caucasian in-patients with MDD and 25 matched controls under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 56 publications
(59 reference statements)
4
17
0
Order By: Relevance
“…MD patients exhibit a reduced visual arousal in the right TPJ [49]. Treatment elevated TPJhypoactivity towards activity levels of healthy controls [50]. These studies corroborate a role of the TPJ in enabling internal predictions about external sensory events [51], which might be altered in MD.…”
Section: Discussionsupporting
confidence: 60%
“…MD patients exhibit a reduced visual arousal in the right TPJ [49]. Treatment elevated TPJhypoactivity towards activity levels of healthy controls [50]. These studies corroborate a role of the TPJ in enabling internal predictions about external sensory events [51], which might be altered in MD.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with previous findings in depressed patients (Domschke et al, 2015, Kayser et al, 2000, Kayser et al, 2001, Moratti et al, 2008, Zwanzger et al, 2016), particularly in those with a family history of depression (Moratti et al, 2015), we found that an early, emotion-specific right-lateralized activation of occipitotemporal cortex at around 200 ms post stimulus onset was less robust in high compared with low risk individuals. Even stronger reductions of these early emotional effects were observed for individuals with a lifetime history of MDD compared to those without; however, the present analysis indicated these effects were unrelated and not necessarily additive.…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to a failure to allocate more attention to motivationally significant stimuli via re-entrant subcortical feedback of anterior brain regions to visual cortex (e.g., Keil et al, 2009, Keil et al, 2012, Moratti et al, 2011, Sabatinelli et al, 2007, Sabatinelli et al, 2013), or because of active, prefrontal top-down regulation of these posterior regions (Pessoa, 2008, Tang et al, 2015), or both. Either way, early onset and putative origin of these effects in right extrastriate cortex strongly suggests attentional modulation that preceded conscious awareness of motivationally salient stimuli (Domschke et al, 2015, LeDoux, 1989, LeDoux, 2015, Tamietto and de Gelder, 2010). Moreover, the spatial localization appears to complement previous reports of right temporoparietal cortical thinning and greater EEG alpha in individuals with parental depression (Bruder et al, 2005, Bruder et al, 2007, Bruder et al, 2012, Peterson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the negative arousal-related emotional ERP effects, which include an early right-greater-than-left asymmetry over occipitotemporal regions that is modulated by hemifield, may be rather universal. However, we and others have found marked reductions of emotional ERP modulations in clinically-depressed patients suggesting hypofunction of right temporoparietal regions (e.g., Foti et al, 2010; Kayser et al, 2000, 2001; Moratti et al, 2008), and recent electrophysiologic evidence indicates that blunted responses to emotionally-arousing stimuli in major depression may serve as a possible biomarker of treatment success (Domschke et al, 2015; Zwanzger et al, 2016). Moreover, similar electrophysiological deficits may even be present in individuals at high family risk for depression (Moratti et al, 2015), as found with a preliminary analysis for a subsample of this cohort (Kayser et al, 2014).…”
Section: Discussionmentioning
confidence: 55%